Minimally invasive approach for adrenal lesions: Systematic review of laparoscopic versus retroperitoneoscopic adrenalectomy and assessment of risk factors for complications. (April 2016) - Conzo, G.; Tartaglia, E.; Gambardella, C.; Esposito, D.; Sciascia, V.; Mauriello, C.; Nunziata, A.; Siciliano, G.; Izzo, G.; Cavallo, F.; Thomas, G.; Musella, M.; et al.
Abstract: In the last decades, minimally invasive transperitoneal laparoscopic adrenalectomy has become the standard of care for surgical resection of the adrenal gland tumors. Recently, however, adrenalectomy by a mininvasive retroperitoneal approach has reached increasingly popularity as alternative technique. Short hospitalization, lower postoperative pain and decrease of complications and a better cosmetic resolution are the main advantages of these innovative techniques. In order to determine the better surgical management of adrenal neoplasms, the Authors analyzed and compared the feasibility and the postoperative complications of minimally invasive adrenalectomy approaches. A systematic research of the English literature, including major meta-analysis articles, clinical randomized trials, retrospective studies and systematic reviews was performed, comparing laparoscopic transperitoneal adrenalectomy versus retroperitoneoscopic adrenalectomy. Many studies support that posterior retroperitoneal adrenalectomy is superior or at least comparable to laparoscopic transperitoneal adrenalectomy in operation time, pain score, blood loss, hospitalization, complications rates and return to normal activity. However, laparoscopic transperitoneal adrenalectomy is up to now a safe and standardized procedure with a shorter learning curve and a similar low morbidity rate, even for tumors larger than 6 cm. Nevertheless, further studies are needed to objectively evaluate these techniques, excluding selection bias and bias related to differences in surgeons' experiences with this approaches.